2004
DOI: 10.1002/pros.20046
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of cathepsin X in prostate cancer and prostatic intraepithelial neoplasia

Abstract: The high expression levels of cathepsin X both in PIN and invasive adenocarcinomas of the prostate suggest that cathepsin X may play a role in the early tumorigenesis of prostate cancer. Further studies are needed to define the utility of this cysteine protease as a diagnostic marker for the early detection of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 37 publications
2
40
2
Order By: Relevance
“…High CtsZ expression correlates with advanced malignancy in hepatocellular carcinomas and colorectal and prostate cancer (Hidaka et al 2000;Nagler et al 2004;Wang et al 2011;Vizin et al 2012). Interestingly, CtsZ is also up-regulated in the inflammatory condition of Helicobacter pyloriassociated gastritis, further increased in gastric cancer, and induced in both infiltrating macrophages and epithelial cells (Krueger et al 2005;Bernhardt et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High CtsZ expression correlates with advanced malignancy in hepatocellular carcinomas and colorectal and prostate cancer (Hidaka et al 2000;Nagler et al 2004;Wang et al 2011;Vizin et al 2012). Interestingly, CtsZ is also up-regulated in the inflammatory condition of Helicobacter pyloriassociated gastritis, further increased in gastric cancer, and induced in both infiltrating macrophages and epithelial cells (Krueger et al 2005;Bernhardt et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compared with other cathepsins, relatively little is known about the roles of CtsZ in cancer. Analysis of patient samples has revealed a correlation between high CtsZ expression levels and advanced malignancy in hepatocellular carcinomas and colorectal, gastric, and prostate cancer (Hidaka et al 2000;Nagler et al 2004;Krueger et al 2005;Wang et al 2011;Vizin et al 2012), suggesting potential cancer-promoting functions in different tumor microenvironments.To investigate the relative roles of CtsZ in TAMs and cancer cells in vivo, we used the RIP1-Tag2 (RT2) PanNET model, in which the SV40 T antigen (Tag) viral oncogene is specifically expressed in b cells of the pancreatic islets under the control of the rat insulin promoter (RIP) (Hanahan 1985). SV40 Tag expression inactivates p53 and pRb, resulting in the development of PanNETs through a stereotypical progression from hyperplastic islets to angiogenic islets and finally multiple end-stage tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…of triplicate wells. carcinomas, and related to the invasiveness of tumour cells (Kruger et al, 2005;Nagler et al, 2004). However, it has been demonstrated that it does not contribute to ECM degradation or affect ECM-dependent cell migration (Kos et al, 2005;Lechner et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, cancer cells have adopted several ways to overcome this powerful tumor suppressor pathway. Besides mutations in senescence-relevant genes such as p53 , one such mechanism seems to act through lysosomal cathepsins such as cathepsin X, which is upregulated in several cancers ( N ä gler et al, 2004 ;Krueger et al , 2005 ) and has been shown to participate in invasive processes (Sevenich et al , 2010 ). Remarkably, the downregulation of cathepsin X leads to accelerated cellular senescence (Kraus et al , 2011 ).…”
mentioning
confidence: 99%